Comparison of Dry and Gel Based Electrodes for P300 Brain–Computer Interfaces - Guger, Christoph; Krausz, Gunther; Allison, Brendan Z.; Edlinger, Guenter (Frontiers in Neuroscience, 2012)
Most brain-computer interfaces (BCI) rely on one of three types of signals in the electroencephalogram (EEG): P300s, steady-state visually evoked potentials (SSVEP), and event-related desynchronization (ERD). EEG is typically recorded non-invasively with electrodes mounted on the human scalp using conductive electrode gel for optimal impedance and data quality. The use of electrode gel entails serious problems that are especially pronounced in real-world settings when experts are not available. Some recent work has introduced dry electrode systems that do not require gel, but often introduce new problems such as comfort and signal quality. The principal goal of this study was to assess a new dry electrode BCI system in a very common task: spelling with a P300 BCI. A total of 23 subjects used a P300 BCI to spell the word “LUCAS” while receiving realtime, closed-loop feedback. The dry system yielded classification accuracies that were similar to those obtained with gel systems. All subjects completed a questionnaire after data recording, and all subjects stated that the dry system was not uncomfortable. This is the first field validation of a dry electrode P300 BCI system, and paves the way for new research and development with EEG recording systems that are much more practical and convenient in field settings than conventional systems.